Pokémon : Pokémon Peril [anglicky]. Book 2 - West, Tracey, 1965- (Orchard Books, 2021)
Join Ash and friends as they continue their journey through the strange and exotic Orange Islands!Ash and Misty have found the GS Poké Ball and finally reached the Orange Islands. But they quickly discover that things are very different here - Pokémon are turning pink, and there is an Onix made of crystal. Can Ash, Misty and their new friend Tracey work out what is going on, before Team Rocket sabotage their journey?